2011
DOI: 10.1016/j.jinorgbio.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of arene–Ru(II)–chloroquine complexes of known antimalarial and antitumor activity with human serum albumin (HSA) and transferrin

Abstract: The interactions of π-arene-Ru(II)-chloroquine complexes with human serum albumin (HSA), apotransferrin and holotransferrin have been studied by circular dichroism (CD) and UV-Visible spectroscopies, together with isothermal titration calorimetry (ITC). The data for [Ru(η6-p-cymene)(CQ)(H2O)Cl]PF6 (1), [Ru(η6-benzene)(CQ)(H2O)Cl]PF6 (2), [Ru(η6-p-cymene)(CQ)(H2O)2][PF6]2 (3), [Ru(η6-p-cymene)(CQ)(en)][PF6]2 (4), [Ru(η6-p-cymene)(η6-CQDP)][BF4]2 (5) (CQ: chloroquine; DP: diphosphate; en: ethylenediamine), in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 60 publications
(60 reference statements)
3
44
0
Order By: Relevance
“…Several mechanisms have been proposed to elucidate the anticancer activities of ruthenium complexes, including the inhibition of metastasis, 23,24 interaction with DNA and proteins, 25,26 generation of ROS, 27 induction of apoptosis. 28 Based on our previous work, [29][30][31][32][33] we found that ruthenium(II) polypyridyl complexes appear to show high activity against cancer cells.…”
Section: -22mentioning
confidence: 99%
“…Several mechanisms have been proposed to elucidate the anticancer activities of ruthenium complexes, including the inhibition of metastasis, 23,24 interaction with DNA and proteins, 25,26 generation of ROS, 27 induction of apoptosis. 28 Based on our previous work, [29][30][31][32][33] we found that ruthenium(II) polypyridyl complexes appear to show high activity against cancer cells.…”
Section: -22mentioning
confidence: 99%
“…The binding constant of AdpaMn (K A = 1.86 Â 10 5 M À1 ) is much bigger than that of MnCl 2 , which is similar to that of Ru(II)-complex with transferrin (10 3 to 10 5 M À1 ) [10,22]. Stern-Volmer dynamic quenching constant of AdpaMn (K SV ) is 2.86 Â 10 5 M À1 , which is greater than that of biological macromolecules (K SV < 100 M À1 ), indicating the possible formation of AdpaMn-apoTf complex entity [22,23]. Further, the effect of the other function-related proteins in serum, such as human serum albumin (HSA), on the binding of complexes to apoTf was studied (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…21 Transferrin, in turn, is the protein primarily responsible for transporting iron throughout the body, and it can also bind metallodrugs reversibly. 23-25 In particular, ruthenium complexes with anticancer 20,22,23 or antimalarial 26 properties have been shown to interact with human serum albumin (HSA) and with apotransferrin (ATf). We have now investigated the interactions of HSA and ATf with complexes 1-6 by use of a fluorimetric titration technique.…”
Section: Resultsmentioning
confidence: 99%
“…The values obtained for K indicate a fairly high affinity of the Ru-KTZ complexes for HSA, in the same order of magnitude as those observed by us for related Ru-chloroquine complexes with antimalarial activity. 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation